1.) Solve for x :

xlnx−3+lnx−3x=0

Take ln x as a common factor in the first and third terms, making

(x + 1)ln x

(x + 1)ln x - 3(x+1) = 0

(x+1)(ln x - 3) = 0

Therefore x + 1 = 0 or ln x - 3 = 0

Therefore x = -1 or x = e^3

2)Solve for x :

-2√2(√3 sin x + cos x)^(-2) * (√3 cos x - sin x) = 0 for 0<x<2pi

(√3 sin x + cos x)^2

√3 cos x - sin x = 0

which is equivalent to

tan x = √3

x = pi/3 or 4pi/3

3) Solve for x :

x^3 - x^{5/2} - 6x^2 = 0

i dont know how to do this one ><

The text in read is what i have tried, but something is wrong. Can anyone help me find out what i did wrong?